2006
DOI: 10.2337/db05-1634
|View full text |Cite
|
Sign up to set email alerts
|

Increased Dicarbonyl Metabolism in Endothelial Cells in Hyperglycemia Induces Anoikis and Impairs Angiogenesis by RGD and GFOGER Motif Modification

Abstract: Chronic vascular disease in diabetes isC hronic vascular disease is the major cause of morbidity and mortality in diabetes (1). This is associated with dysfunction of endothelial cells in hyperglycemia (2) and damage to the endothelium; the latter is indicated in vivo by increased detachment and premature death of endothelial cells by apoptosis (including anoikis) (3,4). A cellular marker of damage to the endothelium, increased number of circulating endothelial cells, in diabetes was not linked directly to gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
229
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(238 citation statements)
references
References 47 publications
(68 reference statements)
5
229
1
3
Order By: Relevance
“…Other studies have found degeneration of sciatic nerve and retina characteristic of early-stage diabetic neuropathy and retinopathy in this model [14,15]. Increased tissue content of AGEs in diabetes leads to impairment of protein function, linked to vascular cell detachment and anoikis [16,17], oxidative stress [18], low-grade inflammation [18,19] and other cell dysfunctions implicated in the development of microvascular complications [20]. Thiamine and benfotiamine proba- Data are means±SD; units are mmol/mol lysine for FL, CML and CEL and mmol/mol arginine for G-H1, MG-H1 and 3DG-H Rat study group key as in Table 1 *p<0.05, **p<0.01 and ***p<0.001 with respect to normal control † p<0.05, † † p<0.01 † † † p<0.001 with respect to diabetic controls bly decrease AGE and oxidation and nitration adduct formation by increasing transketolase expression and activity in tissues [3,4,21]; this counters metabolic dysfunction and oxidative stress in hyperglycaemia, maintains antioxidant and dicarbonyl-metabolising enzyme activities and thereby prevents protein damage [2].…”
Section: Discussionmentioning
confidence: 53%
“…Other studies have found degeneration of sciatic nerve and retina characteristic of early-stage diabetic neuropathy and retinopathy in this model [14,15]. Increased tissue content of AGEs in diabetes leads to impairment of protein function, linked to vascular cell detachment and anoikis [16,17], oxidative stress [18], low-grade inflammation [18,19] and other cell dysfunctions implicated in the development of microvascular complications [20]. Thiamine and benfotiamine proba- Data are means±SD; units are mmol/mol lysine for FL, CML and CEL and mmol/mol arginine for G-H1, MG-H1 and 3DG-H Rat study group key as in Table 1 *p<0.05, **p<0.01 and ***p<0.001 with respect to normal control † p<0.05, † † p<0.01 † † † p<0.001 with respect to diabetic controls bly decrease AGE and oxidation and nitration adduct formation by increasing transketolase expression and activity in tissues [3,4,21]; this counters metabolic dysfunction and oxidative stress in hyperglycaemia, maintains antioxidant and dicarbonyl-metabolising enzyme activities and thereby prevents protein damage [2].…”
Section: Discussionmentioning
confidence: 53%
“…The interruption of this connection to the ECM has detrimental effects on cell survival, leading to a specific type of apoptosis called anoikis in most non-transformed cell types (Reddig and Juliano, 2005). Dobler et al (2006) recently reported that the chronic vascular disease of diabetes is associated with a disruption of endothelial cell adhesion to its ECM, endangering cell survival and vascular structure. The authors show that methylglyoxal, a precursor of AGEs whose formation is increased in hyperglycemia, causes a strong change in the binding sites of integrins to type IV collagen of the vascular basement membrane, causing endothelial cell detachment, anoikis, and inhibition of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in diabetic patients the early stages of microangiopathy is characterized by the development of acellular capillaries and decreased angiogenesis with consequent ischaemia [158]. Interestingly, Dobler reported that methylglyoxal, a dicarbonyl glycating agent whose formation is improved in hyperglycaemia, provokes strong modifications in integrin-binding sites of type IV collagen within the vascular basement membrane, causing detachment and anoikis of endothelial cells [159,160]. Thus, increased formation of methylglyoxal and ECM glycation in hyperglycaemia impairs endothelial cell survival and vasculature structure and inhibits angiogenesis, likely contributing to vascular dysfunction in diabetes [159].…”
Section: Anoikis Induction In Cardiovascular Diseases and Diabetesmentioning
confidence: 99%
“…Interestingly, Dobler reported that methylglyoxal, a dicarbonyl glycating agent whose formation is improved in hyperglycaemia, provokes strong modifications in integrin-binding sites of type IV collagen within the vascular basement membrane, causing detachment and anoikis of endothelial cells [159,160]. Thus, increased formation of methylglyoxal and ECM glycation in hyperglycaemia impairs endothelial cell survival and vasculature structure and inhibits angiogenesis, likely contributing to vascular dysfunction in diabetes [159]. Emerging therapeutic interventions aimed at scavenging methylglyoxal prevent the loss of endothelial cells and the impairment of angiogenesis, ultimately inhibiting the vascular complications of diabetes.…”
Section: Anoikis Induction In Cardiovascular Diseases and Diabetesmentioning
confidence: 99%